Physical properties of cinnamon bark - Ashish M Mohite, T John Zachariah, S Balasubramanian, K K Singh, (Journal of Spices and Aromatic Crops, 2012)
Physical properties of cinnamon (Cinnamomum verum J.Pres) bark (var. Nityashree) were determined by dividing into three grades (I, II & III) according to their size at 10.15% (db) moisture content. The values of length, breadth and thickness for grade I were 48.38 mm, 7.34 mm and 1.37 mm; for grade II were 71.81 mm, 8.45 mm and 1.00 mm; for grade III were 104.95 mm, 8.15 mm and 0.98 mm, respectively. Unit volume and surface area for grade I were 214.80 mm3 and 159.68 mm2; for grade II were 364.92 mm3 and 226.33 mm2; for grade III were 409.85 mm3 and 242.85 mm2, respectively. Bulk density and true density for grade I were 144.56 kg m-3 and 177.60 kg m-3 for grade II were 148.44 kg m-3 and 186.87 kg m-3 for grade III were 132.08 kg m-3 and 202.91 kg m-3, respectively. Porosity, angle of repose for grade I was 14.20% and 40.69°; for grade II were 20.95% and 41.56°; for grade III were 37.72% and 42.30°, respectively. The coefficient of static friction with respect to different surfaces viz., plywood, galvanized iron and aluminum sheet for grade I were 0.86, 0.94 and 0.80; for grade II were 0.84, 0.89 and 0.79; for grade III were 0.80, 0.81 and 0.70, respectively.